STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PRESTASI SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS V DI SDN TERPADU BINTUNI - Djahidi, Jaenal Aripin; Rasyid, Muhammad Rusdi (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
This research aims to analyze the process of implementing Islamic religious education teachers' strategies in improving student achievement in class V Islamic religious education subjects at Bintuni Integrated Elementary School, analyzing supporting and inhibiting factors, and analyzing the impact of implementing Islamic religious education teachers' strategies in improving student achievement. This research uses descriptive qualitative research. The primary data source is the Islamic Education Teacher as the main informant and additional informants: the school principal, class teachers, student affairs and students. Secondary data sources: books, magazines, internet, reports and documentation. The data collection methods used were observation, interviews and documentation. The data analysis processing techniques used are data reduction, data presentation and drawing conclusions. The results of the research show that: the strategy of Islamic religious education teachers in improving student achievement in class V Islamic religious education subjects by implementing the Quantum Teaching learning model in accordance with the four teacher learning strategies: identifying and determining student indicators, choosing teaching and learning strategies, choosing KBM procedures, and minimum KBM learning criteria. The duties of teachers are; pedagogical duties, professional duties, personal duties, social duties. Supporting factors are: teachers, student awareness, and family. Inhibiting factors are: Infrastructure suggestions, religious diversity, influence of globalization, time limitations, honorary teachers. The results' impacts are that the Quantum Teaching learning strategy is in accordance with the students' themes, needs and situations. The results of this learning strategy have a positive impact on the learning process and outcomes of Bintuni Integrated Elementary School students.